MELANOCYTOMA OF THE OPTIC NERVE HEAD COEXISTING WITH JUXTAPAPILLARY CHOROIDAL NEVUS: CASE REPORT AND LITERATURE REVIEW: OPTIC NERVE MELANOCYTOMA WITH CHOROIDAL NEVUS - Vasović, Dolika; Mitrović, Mirjana; Marjanović, Ivan; Kalezić, Tanja (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Melanocytoma of the optic nerve head (melanocytoma papillae) is a rare, benign pigmented lesion originating from melanocytes within the optic nerve head. Despite its benign nature, melanocytoma can present diagnostic challenges due to its potential mimicry of malignant melanomas and associated complications, including visual field defects and, in rare cases, malignant transformation. Accurate diagnosis relies on multimodal imaging, including fluorescein angiography, optical coherence tomography (OCT), and enhanced depth imaging-OCT (EDI-OCT). Case report: A 40-year-old female presented with a pigmented lesion on the left optic nerve head, which had been monitored at another institution for the past 10 years. Ophthalmologic examination revealed a sharply demarcated, elevated, gray-black lesion with clinical features typical of melanocytoma. Adjacent to the melanocytoma, a juxtapapillary choroidal nevus was observed. The diagnostic workup, including fluorescein angiography and B-scan ultrasonography, confirmed the benign nature of the lesion. The patient was advised to undergo regular follow-up to monitor for potential progression or malignant transformation. Conclusion: This case underscores the importance of auxiliary diagnostic methods and long-term surveillance in managing melanocytoma of the optic nerve head. The coexistence of a juxtapapillary choroidal nevus further complicates the diagnostic process, emphasizing the need for regular follow-up to enable the timely detection of potential complications.